2020
DOI: 10.1101/2020.03.21.001693
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CTCF Promotes Long-range Enhancer-promoter Interactions and Lineage-specific Gene Expression in Mammalian Cells

Abstract: 23 24 [All datasets have been deposited to GEO, with accession number GSE94452, and can be 25 accessed here]. 26 3 Abstract: 27 Topologically associating domains (TAD) and insulated neighborhoods (INs) have been 28 proposed to constrain enhancer-promoter communications to enable cell-type specific 29 transcription programs, but recent studies show that disruption of TADs and INs resulted in 30 relatively mild changes in gene expression profiles. To better understand the role of 31 chromatin architecture in dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
12
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 85 publications
(109 reference statements)
7
12
3
Order By: Relevance
“…2c-d). This indicates that CTCF is required for the expression of thousands of genes during zebrafish development, an impacting result that contrasts to previous observations in in vitro experimental setups showing alteration of a few hundred genes upon CTCF removal 5,32 . Next, we analyzed gene expression changes in the transition from 24 to 48 hpf in wild-type embryos and found that genes that get activated in this period tend to be down-regulated in ctcf −/− embryos, and vice versa, indicating that many developmental genes fail to acquire their normal expression level during this developmental period (Extended Data Fig.…”
Section: Developmental Gene Expression Requires Ctcfcontrasting
confidence: 90%
See 3 more Smart Citations
“…2c-d). This indicates that CTCF is required for the expression of thousands of genes during zebrafish development, an impacting result that contrasts to previous observations in in vitro experimental setups showing alteration of a few hundred genes upon CTCF removal 5,32 . Next, we analyzed gene expression changes in the transition from 24 to 48 hpf in wild-type embryos and found that genes that get activated in this period tend to be down-regulated in ctcf −/− embryos, and vice versa, indicating that many developmental genes fail to acquire their normal expression level during this developmental period (Extended Data Fig.…”
Section: Developmental Gene Expression Requires Ctcfcontrasting
confidence: 90%
“…The interaction profile was generally characterized by a loss of long-range contacts but retaining some contacts at shorter ranges (Fig. 4a), consistent with observations in mammalian cells 32,44 . Genomic regions showing a reduced contact frequency with the ptch2 promoter included CTCF-binding sites as well as ATAC peaks with reduced accessibility in the mutant and others not affected by CTCF absence.…”
Section: Ctcf Is Required For the Spatiotemporal Expression Patterns supporting
confidence: 87%
See 2 more Smart Citations
“…In line with this, Bing Ren lab recently revealed that disruption of CTCF binding on the promoter led to reduction of promoter–enhancer interaction and decreased transcription, while artificial tethering of CTCF on the promoter led to restoration of enhancer–promoter interaction and transcription. Moreover, the occupancy of CTCF on the promoter is associated with cell-specific transcription ( 87 ). In addition, Keji Zhao lab uncovered that CTCF could bring distal enhancer to the vicinity to their target genes via interaction with cohesin ( 88 ).…”
Section: Alteration Of Chromatin Topology In Carcinogenesismentioning
confidence: 99%